2017
DOI: 10.1111/aor.12863
|View full text |Cite
|
Sign up to set email alerts
|

Ozone Prevents Cochlear Damage From Ischemia–Reperfusion Injury in Guinea Pigs

Abstract: The cochlea is an end organ, which is metabolically dependent on a nutrient and oxygen supply to maintain its normal physiological function. Cochlear ischemia and reperfusion (IR) injury is considered one of the most important causes of human idiopathic sudden sensorineural hearing loss. The aim of the present study was to study the efficacy of ozone therapy against cochlear damage caused by IR injury and to investigate the potential clinical use of this treatment for sudden deafness. Twenty-eight guinea pigs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
(49 reference statements)
0
13
0
4
Order By: Relevance
“…Then, caspase‐3 activates the caspase‐activated DNAase, leading to DNA fragmentation. It was reported that ozone could reduce the apoptosis of rat retina (Kal et al, 2017) and pig cochlear tissues induced by I/R injury (Onal et al, 2017). Our study showed that ozone significantly inhibited SH‐SY5Y cells apoptosis compared with group I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Then, caspase‐3 activates the caspase‐activated DNAase, leading to DNA fragmentation. It was reported that ozone could reduce the apoptosis of rat retina (Kal et al, 2017) and pig cochlear tissues induced by I/R injury (Onal et al, 2017). Our study showed that ozone significantly inhibited SH‐SY5Y cells apoptosis compared with group I/R.…”
Section: Discussionmentioning
confidence: 99%
“… Histological evaluation : increased numbers of glial cells in the spiral ganglion, reduced level of vascularization. ( Onal et al, 2017 ) Postconditioning : 60 ug/mL, rectal and/or intratympanic, 7 days, after cisplatin-induced ototoxicity (5-mg/kg/day). The rats were tested with distortion product otoacoustic emissions (DPOAE).…”
Section: Effect Of Ozone Oxidative Preconditioning On Oxidative Stresmentioning
confidence: 99%
“…The cochlea is an end organ, which is metabolically dependent on a nutrient and oxygen supply to maintain its normal physiological function. It is very sensitive to alterations in blood circulation [14]. Cochlear ischaemia is considered to be one of the most important causes of idiopathic SSNHL [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hearing loss associated with hyperlipidaemia tends to improve with diet control and antilipemic therapy [23, 24]. Data from animal studies have shown that diet-induced hyperlipidaemia causes structural and functional changes in the inner ear and that these changes are associated with hearing loss in a time-dependent manner [13, 14, 25]. However, the relationship between hyperlipidaemia and idiopathic SSNHL is not universally accepted.…”
Section: Introductionmentioning
confidence: 99%